Drug Release via Ultrasound-Activated Nanocarriers for Cancer Treatment: A Review - Khaled Armouch Al Refaai; Nour A. AlSawaftah; Waad Abuwatfa; Ghaleb A. Husseini (MDPI AG, 2024)
Conventional cancer chemotherapy often struggles with safely and effectively delivering anticancer therapeutics to target tissues, frequently leading to dose-limiting toxicity and suboptimal therapeutic outcomes. This has created a need for novel therapies that offer greater efficacy, enhanced safety, and improved toxicological profiles. Nanocarriers are nanosized particles specifically designed to enhance the selectivity and effectiveness of chemotherapy drugs while reducing their toxicity. A subset of drug delivery systems utilizes stimuli-responsive nanocarriers, which enable on-demand drug release, prevent premature release, and offer spatial and temporal control over drug delivery. These stimuli can be internal (such as pH and enzymes) or external (such as ultrasound, magnetic fields, and light). This review focuses on the mechanics of ultrasound-induced drug delivery and the various nanocarriers used in conjunction with ultrasound. It will also provide a comprehensive overview of key aspects related to ultrasound-induced drug delivery, including ultrasound parameters and the biological effects of ultrasound waves.